Arranjo de antenas impressas com diagrama de irradia??o reconfigur?vel por fibras de cristiais fot?nicos h?bridas - Patr?cio, Simon Carmo (2015)
This work presents the development of an optically-controlled reconfigurable antenna array at 5.8GHz frequency. The array presents compact dimensions due small dimensions of the antennas. By adjusting each element excitation current amplitude the radiation pattern control is obtained. Optically control on the element current with radio over fiber (RoF) technology is applied through hybrid photonic crystal fibers (HPCF). In this way, one can exploit the HPCF bending loss and/or strong wavelength-dependence chromatic dispersion in manipulating current amplitudes. In the first setup, it was utilized the printed antenna array based on Sierpinski carpet fractal elements. This array was projected to obtain a more directive radiation pattern and introduce changes in the maximum radiation beam direction when reconfigured. After inserting the reflector plane, it was demonstrated the improved directivity of the array increasing the signal to noise ratio (SNR) and decreasing the bit error rate (BER) at the reception by received signals with QPSK modulation and 16-QAM. In the second setup was utilized an antenna array based on three printed half-wavelength dipoles. An efficient scheme in controlling the radiation pattern of an antenna array based on photonics technology was demonstrated with almost equal measured and simulated results.